Your coworkers can make you sick: An investigation of coworker undermining and employee health - Costa, S.; Velez, M. J.; Lopéz, A. (Journal of Occupational and Organizational Psychology, 2024)
Although mistreatment in the workplace has been widely acknowledged, the impact of coworker undermining has not been adequately explored in the literature. Using insights from the job demands–resources model, we suggest that coworker undermining is a job demand that is associated with negative affect and somatic complaints. In mitigation of this, we propose two personal resources (i.e. forgiveness and revenge cognitions) as buffers of the positive relationship between coworker undermining and somatic complaints via negative affect. We explore these relationships in a time-lagged study involving 229 participants who responded to three surveys over a month-long period. Our findings show that coworker undermining is related to high levels of negative affect in the following week, and that this spills over to somatic complaints. However, this is only true for victims of undermining who do not forgive their colleagues.